(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
Marketing and advertising strategies to increase the positioning of the commercial company and increase visibility in the market in order to reach the potential user. The main problem with this line of business is that it does not have any advertising and marketing strategy. Every company has its own strategic plan to achieve its objectives and goals to achieve, these can be at different times depending on the breadth and magnitude of each organization. Observing the great opportunity of the sectors that it has to offer, in various cities of the country, a proposal for a strategic marketing plan will be designed, focused on advertising to increase presence in the market and thus increase sales to increase income.